(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In the article, the author reveals the role of the educator in artistic and aesthetic development, how it influences the formation of children’s aesthetic attitude to the environment: development of the ability to see and feel beauty in nature, actions, art, to understand the beautiful; education of artistic taste, the need to know the beautiful through the author’s program "World of Wizards".